A Cost-Effective Physiotherapy and Allied Health Program to Improve Education, Independent Function, and Reduce Falls in Patients with Parkinson’s Disease (International Journal of Physiotherapy, 2025)
Background: Parkinson’s is a degenerative neurological condition of increasing incidence globally. There are a broad range of motor and non-motor symptoms individually experienced. Falls can be common and can increase the risk of fractures with consequent, potential complications of a possible hospital admission. Early-stage education, promoting informed self-management including engagement in exercise, may reduce the associated consequences of reduced mobility, confidence and quality of life. This paper describes an inexpensive allied health led programme of exercise and education that aims to improve quality of life, reduce falls and promote self-managment. It promotes a proactive rather than reactive approach to Early Parkinson’s care.Methods: Ten volunteer patients with Parkinson’s Disease were recruited into a ten-week allied health program combining education about the condition and a course of physiotherapy led exercise to improve mobility and reduce falls.Results: Objective testing revealed an overall marked improvement in mobility and a reduced risk of falling. Developing knowledge and camaraderie between staff, patients, and relatives significantly improved the the patients's self-management and improved mental health.Conclusion: Activities of daily living can be significantly enhanced in Parkinson’s Disease patients with an inexpensive allied health plan.